1994
DOI: 10.1073/pnas.91.23.11070
|View full text |Cite
|
Sign up to set email alerts
|

Spatially controlled adhesion, spreading, and differentiation of endothelial cells on self-assembled molecular monolayers.

Abstract: Chenaically moid glass substrates were used to denste dirental adheso, growth, and differention f endoel cells. Endothellal cells were eamine for Madei and growth on glass, glass treated with N-(2-aminethyl)-3-amnopropyl trimethoxysilane (EDA) Several approaches have also demonstrated the potential for controlling the spatial distribution of cells on the surface. Carter (8, 9) and later Harris (10), using acetate-coated glass, created palladium islands and channels for studying single fibroblast cell reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 25 publications
3
86
0
Order By: Relevance
“…32 Its role in patterning applications as the cell-permissive substrate that is surrounded by noncell permissive SAMs is further strengthened because it is not degraded by the cells. 31,42 This characteristic of DETA allows it to form sharp patterns that do not blend with the noncell permissive PEG background and promotes pattern stability under long-term culture conditions. 25,31 PEG SAMs prevent the adsorption of proteins on glass surfaces by the entropy/hydrated surface hypothesis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…32 Its role in patterning applications as the cell-permissive substrate that is surrounded by noncell permissive SAMs is further strengthened because it is not degraded by the cells. 31,42 This characteristic of DETA allows it to form sharp patterns that do not blend with the noncell permissive PEG background and promotes pattern stability under long-term culture conditions. 25,31 PEG SAMs prevent the adsorption of proteins on glass surfaces by the entropy/hydrated surface hypothesis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Many reports have confirmed the effect of soluble factors and surface chemistry on the initial adhesion and proliferation of cells [18,19]. In nature, multivalent interactions are involved in cellecell communications and celleECM interactions.…”
Section: Introductionmentioning
confidence: 92%
“…Ligand clustering changes the receptor distribution in a dynamic way and regulates multipoint and strong attachment [20]. Depending on the ligand arrangement on the surface, it has been demonstrated that the surface chemistry not only plays a significant role in initial adhesion but may also control the signaling processes leading to different differentiation pathways [19]. The ligand arrangement and density along with the physical characteristics of the underlying substrate can modulate cell behavior independently as well as collectively.…”
Section: Introductionmentioning
confidence: 99%
“…235 A range of techniques have been used to micropattern endothelial cells. [236][237][238][239][240][241][242][243] Chen et al 244 found that cell spreading acted as a regulator of proliferation or death in human and bovine capillary endothelial (CE) cells by tightly controlling cell spreading with adhesive microislands of fibronectin; fibronectin was adsorbed on a methyl-terminated alkanethiol SAM, whereas the nonadhesive background consisted of a hexaethylene-glycolterminated alkanethiol SAM (HEG-SAM) that resisted protein adsorption and cell attachment. Cells that were free to spread over large microislands displayed growth, as expected, but the cells that were constrained to limit their spreading to a small island displayed apoptosis.…”
Section: Ve Endothelial Cell Biology On a Chipmentioning
confidence: 99%